High-performance copper bus and preparation method thereof

Through the mixing of composite aerogel and copper powder and the doping of specific elements, combined with the use of thermally conductive and anti-corrosion coating materials, the problems of insufficient oxidative corrosion, electrical conductivity and heat dissipation capabilities of the copper busbar are solved, and its mechanical properties are significantly improved and anti-corrosion properties extend service life.

CN119252560AActive Publication Date: 2025-01-03QINGYUAN KAIYU PROJECT SUPERVISION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411435473.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-03
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing copper bus bars are prone to oxidation and corrosion in the air, and lack of conductivity and heat dissipation capabilities, resulting in an increase in contact resistance and shortened life, and the temperature is too high when high current passes through, and damage.

Method used

Compound aerogel and copper powder are mixed with, and scandium, chromium, lanthanum, cobalt, nickel, silicon, niobium and tantalum are added after ball milling. The copper busbar matrix is ​​formed by pressing, smelting, semi-continuous casting and cross-turning rolling, and coated. Thermal conductive and anti-corrosion coating materials, including modified boron nitride and nano-alumina, form a dense thermally conductive and anti-corrosion coating.

Benefits of technology

It significantly improves the mechanical properties, conductivity, heat dissipation and corrosion resistance of the copper busbar, extends the service life, and enhances the heat transfer effect of the thermal conductivity network and the adhesion of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252560A_ABST
    Figure CN119252560A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductor preparation, and discloses a high-performance copper bus and a preparation method thereof. The preparation method of the high-performance copper bus comprises the following steps: mixing composite aerogel and copper powder, and performing ball milling to obtain composite powder; adding scandium, chromium, lanthanum, cobalt, nickel, silicon, niobium and tantalum, and crushing to obtain mixed powder; compacting and smelting the mixed powder to obtain a melt; carrying out semi-continuous casting on the melt to obtain a copper busbar semi-continuous blank; carrying out homogenization treatment on the copper busbar semi-continuous blank, and then carrying out cross turnover rolling to obtain a copper busbar blank; pressing the copper busbar blank to form a copper busbar substrate; and carrying out mechanical polishing and ultrasonic cleaning treatment on the copper busbar substrate, then coating the copper busbar substrate with the heat-conducting anticorrosive coating material, and curing to obtain the high-performance copper busbar. The high-performance copper bus has good mechanical performance, electrical conductivity, corrosion resistance and heat dissipation and heat conduction capabilities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductor preparation, in particular to a high-performance copper busbar and a preparation method thereof. Background Art

[0002] Copper busbar is a power product that uses copper alloy as a material to combine multiple current-carrying branch circuits in different power devices to achieve the purpose of collecting, distributing and transmitting electrical energy. In the hard state, the main technical performance of the copper busbar is as follows: conductivity ≥ 97% IACS, hardness ≥ 65HB, bending ≥ 90° according to the requirements of the national standard GB / T5585-2005. However, with the progress of society, the circuit usage of enterprises is getting higher and higher, and the requirements for busbars are getting higher and higher. For example, Chinese patent CN104599787B provides a preparation method of high-performance copper busbar, which includes the following production process steps: A copper material selection; B copper material melting; C copper liquid standing; D copper liquid insulation; E continuous casting copper rod; F continuous extrusion; G drawing forming, its conductivity ≥ 100.3% IACS, hardness ≥ 85HB, but because the copper busbar is easily oxidized and corroded in the air, it will affect the contact resistance of the busbar overlap surface and shorten the life of the busbar. In addition, when working, due to a large amount of current passing through the busbar, the busbar temperature is too high, which will cause damage to the busbar. It is also necessary to improve the heat dissipation and thermal conductivity and corrosion resistance of the copper busbar. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing a high-performance copper busbar, comprising the following steps:

[0004] Step (1), mixing the composite aerogel with copper powder, ball milling to obtain composite powder; then adding scandium, chromium, lanthanum, cobalt, nickel, silicon, niobium and tantalum, crushing to obtain mixed powder;

[0005] The preparation method of the composite aerogel comprises the following steps:

[0006] Step B1: Using MAX phase Ti 3 AlC 2 powder as a raw material to prepare MXene powder; modifying the MXene powder to obtain modified MXene;

[0007] Step B2, first preparing silica aerosol, and then using the silica aerosol and modified MXene as raw materials to prepare a composite aerogel;

[0008] Step (2), the mixed powder is pressed and smelted to obtain a melt; the melt is semi-continuously cast to obtain a semi-continuous billet of a copper busbar;

[0009] Step (3), homogenizing the copper busbar semi-continuous billet, and then performing cross-rolling to obtain a copper busbar billet; the copper busbar billet is pressed to form a copper busbar matrix;

[0010] Step (4), mechanically polishing and ultrasonically cleaning the copper busbar substrate, then coating the copper busbar substrate with a thermal conductive anti-corrosion coating material, and curing the coating to obtain a high-performance copper busbar;

[0011] The preparation method of the thermal conductive anti-corrosion coating material comprises the following steps:

[0012] Step A1, first prepare cerium carbonate, and then react with methacrylic acid to obtain cerium methacrylate; modify boron nitride with cerium methacrylate to obtain modified boron nitride;

[0013] Step A2, dopamine hydrochloride reacts with methacrylic anhydride to obtain an intermediate product; the intermediate product reacts with modified boron nitride to obtain a composite hybrid;

[0014] Step A3, modifying the nano-alumina with 3-aminopropyltrimethoxysilane to obtain modified nano-alumina;

[0015] A water-based epoxy resin and a composite hybrid are mixed, and then modified nano-alumina, a wetting dispersant, a polyetheramine curing agent, a defoaming agent, and a leveling agent are added to obtain a thermal conductive anti-corrosion coating material.

[0016] Preferably, in the step (1), the mass ratio of the composite aerogel to the copper powder is (0.3-0.6):100; the ball milling conditions are: the grinding medium is stainless steel balls, the ball-to-material ratio is 5:1, the ball milling speed is 100-200 r / min, and the ball milling time is 8-10 h.

[0017] Preferably, in step (1), the particle size of the mixed powder is 20-50 mm; the contents of the components in the mixed powder are: scandium 0.1-0.4wt%, chromium 1-1.6wt%, lanthanum 0.05-0.15wt%, cobalt 0.8-1.4wt%, nickel 1.2-1.6wt%, silicon 0.5-0.8wt%, niobium 0.06-0.1wt%, tantalum 0.8-1.2wt%, and the rest are composite powders.

[0018] Preferably, in step (2), the pressing pressure is 250-300 MPa; the smelting conditions are: temperature is 1000-1200° C., and time is 3-5 h.

[0019] Preferably, in the step (3), the temperature of the homogenization treatment is 780-840° C.; the copper busbar blank is obtained after 1-2 cycles of 3-6 passes of cross rolling.

[0020] Preferably, in the step (4), the copper busbar substrate is mechanically polished to have a surface roughness Ra≤0.15 μm.

[0021] Preferably, in step (4), the curing conditions are: curing at 70-90° C. for 1.5-2.5 hours; the thickness of the thermal conductive anti-corrosion coating after curing is 2-6 μm.

[0022] Preferably, in step (1), the method for preparing the composite aerogel comprises the following steps:

[0023] Step B1: at room temperature, 3 AlC 2 The powder is added to 48 wt% hydrofluoric acid within 10-20 min, stirred for 20-40 min, and then stirred in an oil bath at 40-60 ° C for 12-15 h. After the reaction, centrifuge, wash, and dry to obtain MXene powder; wherein the MAX phase Ti 3 AlC 2 The ratio of powder to hydrofluoric acid is (2-4) g: (40-100) mL;

[0024] Add MXene powder to deionized water, and perform ultrasonic treatment for 20-40 minutes to obtain a suspension; dissolve silver nitrate in deionized water, and then add it to the suspension, stir and react in an ice bath for 100-150 minutes, collect the obtained precipitate, wash, and dry to obtain modified MXene; wherein the mass ratio of MXene powder to silver nitrate is (2.5-3.5):(0.05-0.1);

[0025] In the above process, the MAX phase Ti 3 AlC 2 The powder is used as raw material to obtain MXene powder with a nano-sheet microstructure. MXene has excellent conductivity. The presence of hydrofluoric acid and water leads to the generation of a large number of reactive groups on the surface of MXene, including -OH, -COOH and -F. These functional groups carry negative charges and show strong electrostatic attraction to the exogenously added silver nitrate, making Ag + Obtaining electrons from MXene, thereby reducing silver nitrate in situ to form nanosilver, which is deposited on the MXene nanosheets and between the sheets to obtain modified MXene; the deposition of nanosilver forms better thermal and electrical conductive paths between the MXene nanosheets, thereby improving the thermal conductivity and electrical conductivity of the MXene nanosheets;

[0026] Step B2, adding tetraethyl orthosilicate to ethanol, stirring for 10-20 minutes, adding ultrapure water, stirring for 20-40 minutes, adjusting the pH to 2 with a 0.1 mol / L sulfuric acid aqueous solution, stirring at 30-40° C. and 400-500 r / min for 1-2 hours to obtain a silica aerosol; wherein the mass ratio of tetraethyl orthosilicate, ethanol, and ultrapure water is (2.1-2.6):(2.3-2.8):(0.4-0.7);

[0027] Add a 2 mg / mL modified MXene aqueous dispersion to the silica aerosol, adjust the pH to 7 with 0.5 mol / L ammonia water, stir for 10-15 min, seal, and stand at 40-50 ° C until the gel is complete to obtain a hybrid wet gel; the amount ratio of silica aerosol to modified MXene aqueous dispersion is (1.2-2.4) g: (12-36) mL;

[0028] The hybrid wet gel is first immersed in an ethanol aqueous solution with a volume fraction of 80% and is constantly aged at 48-52°C for 22-26h, then immersed in isopropanol and solvent exchanged at 38-42°C for 10-15h, then immersed in n-hexane and solvent exchanged at 38-42°C for 10-15h, the solvent is discharged, dried at room temperature for 12-36h, and then graded dried at 40-60°C and 100-120°C for 1.5-2.5h each to obtain a composite aerogel;

[0029] In the above process, the hydroxyl and other functional groups on the surface of the modified MXene nanosheets fully contact and react with the hydroxyl groups on the surface of the silica spheres formed by tetraethyl silicate, and form a three-dimensional network porous structure with the help of hydrogen bonds, van der Waals forces, etc., and ethanol is filled into the pores of the three-dimensional network porous structure as a filler. Under the catalysis of ammonia water, the silica spheres and the two-dimensional material MXene are cross-linked to form a gel. The addition of modified MXene nanosheets makes the composite aerogel have good conductivity and can improve the thermal conductivity of the aerogel material.

[0030] Preferably, in step (4), the method for preparing the thermal conductive anti-corrosion coating material comprises the following steps:

[0031] Step A1, under the stirring condition of 150-250r / min, cerium (III) nitrate hexahydrate, ammonium bicarbonate and deionized water are mixed, stirred at room temperature for 3-5h, filtered, washed and dried to obtain cerium carbonate; wherein the mass ratio of cerium (III) nitrate hexahydrate, ammonium bicarbonate and deionized water is (6-9):(3-5):(80-100);

[0032] Add cerium carbonate and methacrylic acid into deionized water, stir and react at 85-95° C. and 150-250 r / min for 2-4 hours, and dry after the reaction to obtain cerium methacrylate; wherein the mass ratio of cerium carbonate, methacrylic acid and deionized water is (2-3):(4.5-6.5):(80-120);

[0033] At 70-80° C., cerium methacrylate is dissolved in deionized water, and then boron nitride powder is added, stirred and reacted for 2.5-3.5 hours, and the solvent is distilled off to obtain modified boron nitride; wherein the mass ratio of cerium methacrylate, deionized water, and boron nitride powder is (1-3):(100-200):(6-8);

[0034] In the above process, cerium (III) nitrate hexahydrate and ammonium bicarbonate are reacted through double decomposition to form cerium carbonate, and cerium carbonate and methacrylic acid are reacted through double decomposition to synthesize cerium methacrylate nanoparticles; cerium methacrylate is easily dissolved in deionized water and recrystallized after the water is completely evaporated, so cerium methacrylate is dissolved in deionized water, and then boron nitride powder is added and evaporated and recrystallized, and boron nitride with surface π-electron-rich characteristics is introduced during the recrystallization process, and due to the "cation-π" effect, active nucleation sites can be provided for the recrystallization of cerium methacrylate, and cerium methacrylate is evenly dispersed on the surface of boron nitride;

[0035] Step A2, adding sodium borate and sodium bicarbonate to distilled water, and degassing with nitrogen bubbling for 20-40 minutes, and then adding dopamine hydrochloride to obtain a mixed solution; dissolving methacrylic anhydride in tetrahydrofuran, and then dripping it into the above mixed solution at a rate of 1-2mL / min, adjusting the pH of the reaction system to 8-8.5 with a sodium hydroxide aqueous solution having a concentration of 1 mol / L, stirring the reaction under nitrogen bubbling for 13-15 hours at room temperature to form a white slurry solution, washing with ethyl acetate 2-3 times, filtering, and purifying to obtain an intermediate product; wherein the mass ratio of sodium borate, sodium bicarbonate, distilled water, dopamine hydrochloride, methacrylic anhydride, and tetrahydrofuran is (10-20):(4-8):(100-200):(5-10):(4.7-9.4):(20-40);

[0036] The intermediate product, azobisisobutyronitrile and modified boron nitride are added to N,N-dimethylformamide, the reaction mixture is bubbled with nitrogen for 20-40 minutes, and then the polymerization reaction is carried out at 55-65°C for 2.5-3.5 hours. After the reaction is completed, centrifugation, washing and drying are performed to obtain a composite hybrid; wherein the mass ratio of the intermediate product, azobisisobutyronitrile, modified boron nitride and N,N-dimethylformamide is (6-8):(0.04-0.08):(3-6):(100-250);

[0037] In the above process, the amino group of dopamine hydrochloride reacts with methacrylic anhydride to obtain an intermediate product containing an amide group, a phenolic hydroxyl group, and a carbon-carbon double bond; the intermediate product and the double bond introduced by methacrylic acid on the surface of the modified boron nitride are polymerized under the initiation of azobisisobutyronitrile, and the structure containing an amide group and a phenolic hydroxyl group is introduced into the surface of the modified boron nitride to form a composite hybrid;

[0038] Step A3, mixing ethanol and deionized water, adding 3-aminopropyltrimethoxysilane and nano-alumina, ultrasonically treating for 20-40 minutes, heating to reflux reaction for 10-12 hours, filtering, washing, and drying to obtain modified nano-alumina; wherein the mass ratio of ethanol, deionized water, 3-aminopropyltrimethoxysilane, and nano-alumina is (8-16):(40-80):(0.5-2.5):(2-5);

[0039] In the above process, 3-aminopropyltrimethoxysilane is used to modify the surface of nano-alumina, and amino groups are introduced on the surface of nano-alumina;

[0040] In parts by weight, water-based epoxy resin and composite hybrid are mixed, stirred at a speed of 400-600 r / min for 20-40 min, then modified nano-alumina is added, stirred for 10-20 min, then a wetting dispersant is added, stirred for 20-30 min, a polyetheramine curing agent, a defoaming agent, and a leveling agent are added, stirred for 10-20 min, and a thermal conductive anti-corrosion coating material is obtained;

[0041] Among them, the contents of each component in the thermal conductive anti-corrosion coating material are, by weight: 100-120 parts of water-based epoxy resin, 15-25 parts of composite hybrid, 5-15 parts of modified nano-alumina, 0.3-1.5 parts of wetting dispersant, 5-10 parts of polyetheramine curing agent, 0.5-1.3 parts of defoaming agent, 0.5-1.6 parts of leveling agent; the defoaming agent includes defoaming agent BYK-072, and the leveling agent includes leveling agent BYK-333.

[0042] A high-performance copper busbar is prepared by the method for preparing the high-performance copper busbar.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. The present invention combines composite aerogel, scandium, chromium, lanthanum, cobalt, nickel, silicon, niobium, tantalum and copper powder to prepare a high-performance copper busbar. Through the synergistic effect between the components, the copper busbar matrix has good mechanical properties and conductive properties, which are specifically manifested as follows:

[0045] 1) When La and Sc are doped into the Cu matrix, the combined doping of La and Sc produces a synergistic effect, resulting in high conductivity LaCu 6 Precipitates and high hardness ScCu4 The formation of precipitates promotes high alloying and abundant dislocations, and can induce Ni with excellent mechanical properties. 2 Si and Co 2 The formation of Si precipitates and the precipitation of NiSi phase with high conductivity improve the mechanical properties and electrical conductivity of the copper busbar;

[0046] 2) The composite of chromium, niobium, tantalum and copper can refine the grains and improve the mechanical properties; when cobalt, nickel and silicon are dissolved into the Cu matrix, the electrical conductivity can be improved while improving the mechanical properties;

[0047] 3) The composite aerogel of the present invention has good conductivity due to the doping of modified MXene nanosheets. During the preparation process, the composite aerogel is ball-milled together with copper powder. During the ball milling process, the composite aerogel is densified and collapsed into fine and dispersed hard particles. The micron-sized particles are evenly distributed in the grains and on the grain boundaries. In the process of preparing the copper busbar matrix, nucleation sites are provided for the dynamic recrystallization of the matrix and dynamic recrystallization is promoted. The submicron-sized particles inhibit grain boundary migration. The two-scale reinforcement phase particles work together to greatly refine the grain structure of the copper busbar matrix, thereby making it have excellent conductivity and mechanical properties.

[0048] 2. The cerium methacrylate of the present invention is uniformly dispersed on the surface of boron nitride to obtain modified boron nitride. The inherent high thermal conductivity and good physical barrier ability of two-dimensional boron nitride can give the coating excellent thermal conductivity and corrosion resistance, while the cerium ion and methacrylate ion coating have corrosion inhibition effects. The cerium methacrylate is loaded on the boron nitride to enhance the surface roughness of the nano boron nitride. The micro / nano hierarchical structure exhibits high hydrophobicity, thereby forming an effective triple defense of surface repulsion, self-barrier and double corrosion inhibition, so that the coating material exhibits excellent long-term corrosion resistance; and the cerium methacrylate nanoparticles are uniformly distributed, playing a bridging role in the boron nitride nanosheets, improving the heat transfer effect of the heat conduction network, thereby improving the thermal conductivity of the coating material; further, the intermediate product is connected to the surface of the modified boron nitride, and the phenolic hydroxyl group and amide group in the intermediate product can form hydrogen bonds with the epoxy resin, thereby improving the dispersibility of the modified boron nitride, and forming a strong interaction with the copper busbar substrate, thereby improving the adhesion of the coating material, and making the coating material play a better effect;

[0049] In addition, by surface modification of nano-alumina, it can form a better interface with the composite hybrid and epoxy resin matrix, and the nano-alumina cooperates with the two-dimensional sheet structure of the composite hybrid material to form a more compact thermal conductive and anti-corrosion coating structure, and the spherical shape of the nano-alumina also helps to increase the surface roughness of the coating, thereby enhancing its hydrophobic anti-corrosion performance. Therefore, the thermal conductive anti-corrosion coating of the present invention is coated on the copper busbar substrate to form a thermal conductive and anti-corrosion coating on the surface of the copper busbar substrate, thereby improving the heat dissipation capacity and anti-corrosion performance of the copper busbar. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a process flow chart of a method for preparing a high-performance copper busbar according to the present invention;

[0051] Figure 2 It is a schematic diagram of the synthesis of the intermediate product in the preparation process of the thermal conductive anti-corrosion coating material of the present invention;

[0052] Figure 3 It is a comparison chart of the tensile strength test results of the copper busbar substrates prepared in Examples 3-5 of the present invention and Comparative Examples 7-12;

[0053] Figure 4 It is a comparison chart of the hardness test results of the copper busbar substrates prepared in Examples 3-5 of the present invention and Comparative Examples 7-12;

[0054] Figure 5 It is a comparison chart of the conductivity test results of the copper busbar substrates prepared in Examples 3-5 of the present invention and Comparative Examples 7-12;

[0055] Figure 6 It is a comparison chart of thermal conductivity test results of high-performance copper busbars prepared in Examples 3-5 of the present invention and Comparative Examples 5-6. DETAILED DESCRIPTION

[0056] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0057] Example 1

[0058] This embodiment discloses a method for preparing a thermal conductive anti-corrosion coating material, comprising the following steps:

[0059] Step A1, under the stirring condition of 200r / min, 7.5g of cerium (III) nitrate hexahydrate, 4g of ammonium bicarbonate, and 90g of deionized water are mixed, stirred and reacted at room temperature for 4h, filtered, washed, and dried at 75°C to obtain cerium carbonate; 2.5g of cerium carbonate and 5.5g of methacrylic acid are added to 100g of deionized water, stirred and reacted at 90°C at a speed of 200r / min for 3h, and after the reaction is completed, dried to obtain cerium methacrylate;

[0060] At 75°C, 2 g of cerium methacrylate was dissolved in 150 g of deionized water, and then 7 g of boron nitride powder was added, stirred and reacted for 3 h, and the solvent was distilled off to obtain modified boron nitride;

[0061] Step A2, 15g of sodium borate and 6g of sodium bicarbonate were added to 150g of distilled water, and the mixture was degassed with nitrogen bubbling for 30min, and then 7.5g of dopamine hydrochloride was added to obtain a mixed solution; 7.1g of methacrylic anhydride was dissolved in 30g of tetrahydrofuran, and then added dropwise to the mixed solution at a rate of 1.5mL / min, and the pH of the reaction system was adjusted to 8.2 with a 1mol / L sodium hydroxide aqueous solution, and the mixture was stirred and reacted for 14h at room temperature under nitrogen bubbling to form a white slurry solution, which was washed 3 times with ethyl acetate and filtered. The filtrate was acidified with a 6mol / L hydrochloric acid aqueous solution to a pH of 2, and then extracted with ethyl acetate. The organic layer obtained by the extraction was dried over magnesium sulfate, rotary evaporated to reduce the volume by half, and then hexane was added for precipitation. The resulting suspension was refrigerated at 5°C for 10h, and the resulting solid was dissolved with ethyl acetate and precipitated with hexane, and vacuum dried for 12h to obtain an intermediate product;

[0062] 7g of the intermediate product, 0.06g of azobisisobutyronitrile, and 4.5g of modified boron nitride were added to 180g of N,N-dimethylformamide, and the reaction mixture was bubbled with nitrogen for 30min, and then polymerized at 60°C for 3h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain a composite hybrid;

[0063] Step A3, 12 g of ethanol and 60 g of deionized water were mixed, and then 1.5 g of 3-aminopropyltrimethoxysilane and 3.5 g of nano-alumina were added, and the mixture was ultrasonically treated for 30 min, and the temperature was raised to reflux for reaction for 11 h, and the filtered product was washed with ethanol and vacuum dried at 45° C. to obtain modified nano-alumina;

[0064] In parts by weight, 110 parts of water-based epoxy resin and 20 parts of composite hybrid were mixed, stirred at a speed of 500 r / min for 30 minutes, and then 10 parts of modified nano alumina were added, stirred for 15 minutes, and then 0.9 parts of wetting dispersant were added, stirred for 25 minutes, 7.5 parts of polyether amine curing agent, 0.9 parts of defoaming agent BYK-072, and 1 part of leveling agent BYK-333 were added, and stirred for 15 minutes to obtain a thermal conductive anti-corrosion coating material.

[0065] Example 2

[0066] This embodiment discloses a method for preparing a composite aerogel, comprising the following steps:

[0067] Step B1: at room temperature, 3 g of MAX phase Ti 3 AlC 2 The powder was added to 70 mL of 48 wt% hydrofluoric acid within 15 min, stirred for 30 min, and then stirred in an oil bath at 50 ° C for 13 h. After the reaction, centrifuged, and the obtained precipitate was washed with deionized water until the pH of the washing liquid was 5.5, and then dried at 80 ° C for 13 h to obtain MXene powder;

[0068] 3 g of MXene powder was added to 450 g of deionized water and ultrasonically treated for 30 min to obtain a suspension; 0.08 g of silver nitrate was dissolved in 50 g of deionized water and added to the suspension, and stirred in an ice bath for 120 min. The resulting precipitate was collected and washed with ethanol to remove impurities, and dried at 70 ° C for 12 h to obtain a modified MXene;

[0069] Step B2, adding 2.3 g of tetraethyl orthosilicate to 2.5 g of ethanol, stirring for 15 min, adding 0.6 g of ultrapure water, stirring for 30 min, adjusting the pH to 2 with a 0.1 mol / L aqueous sulfuric acid solution, stirring at 450 r / min at 35° C. for 1.5 h to obtain a silica aerosol;

[0070] 24 mL of 2 mg / mL modified MXe ne aqueous dispersion was added to 1.8 g of silica aerosol, the pH was adjusted to 7 by adding 0.5 mol / L ammonia water, and after stirring for 12 min, the mixture was sealed and allowed to stand at 45°C until the gel was complete to obtain a hybrid wet gel; the hybrid wet gel was first immersed in an ethanol aqueous solution with a volume fraction of 80% and aged at 50°C for 24 h, then immersed in isopropanol and subjected to solvent exchange at 40°C for 12 h, then immersed in n-hexane and subjected to solvent exchange at 40°C for 12 h, the solvent was discharged, dried at room temperature for 24 h, and then graded dried at 50°C and 110°C for 2 h each to obtain a composite aerogel.

[0071] Example 3

[0072] This embodiment discloses a method for preparing a high-performance copper busbar, comprising the following steps:

[0073] Step (1), mixing the composite aerogel and copper powder at a ratio of 0.3:100, and ball milling to obtain composite powder; ball milling conditions: grinding medium is stainless steel balls, ball-to-material ratio is 5:1, ball milling speed is 100 r / min, and ball milling time is 10 h;

[0074] Adding scandium, chromium, lanthanum, cobalt, nickel, silicon, niobium and tantalum to the composite powder to obtain a mixed raw material, and crushing the raw material into a mixed powder with a particle size of 20 mm; wherein the content of each component in the mixed powder is: scandium 0.1wt%, chromium 1wt%, lanthanum 0.05wt%, cobalt 0.8wt%, nickel 1.2wt%, silicon 0.5wt%, niobium 0.06wt%, tantalum 0.8wt%, and the rest is composite powder;

[0075] Step (2), pressing the mixed powder at 250 MPa, placing the pressed powder in a vacuum furnace for smelting, introducing argon into the vacuum furnace, controlling the temperature at 1000° C., smelting for 5 hours to obtain a melt; semi-continuously casting the obtained melt to obtain a semi-continuous copper busbar billet;

[0076] Step (3), homogenizing the copper busbar semi-continuous billet at a temperature of 840° C., and then performing a cross-rolling rolling process for 3 passes in one cycle to obtain a copper busbar billet with uniform thickness; placing the copper busbar billet into a rapid die forging machine and pressing it into a copper busbar substrate of a specified shape;

[0077] Step (4), mechanically polishing the copper busbar substrate to make its surface roughness Ra≤0.15μm, then ultrasonically cleaning the copper busbar with ethanol, and then coating the thermal conductive anti-corrosion coating material on the copper busbar substrate, curing at 70°C for 2.5h, the thickness of the thermal conductive anti-corrosion coating after curing is 2μm, and a high-performance copper busbar is obtained.

[0078] Example 4

[0079] This embodiment discloses a method for preparing a high-performance copper busbar, comprising the following steps:

[0080] Step (1), mixing the composite aerogel and copper powder at a ratio of 0.6:100, and ball milling to obtain composite powder; ball milling conditions: grinding medium is stainless steel balls, ball-to-material ratio is 5:1, ball milling speed is 200 r / min, and ball milling time is 10 h;

[0081] Add scandium, chromium, lanthanum, cobalt, nickel, silicon, niobium and tantalum to the composite powder to obtain a mixed raw material, and crush the raw material into a mixed powder with a particle size of 50 mm; wherein the content of each component in the mixed powder is: scandium 0.4wt%, chromium 1.6wt%, lanthanum 0.15wt%, cobalt 1.4wt%, nickel 1.6wt%, silicon 0.8wt%, niobium 0.1wt%, tantalum 1.2wt%, and the rest is composite powder;

[0082] Step (2), pressing the mixed powder into a green sheet at 300 MPa, placing the green sheet into a vacuum furnace for smelting, introducing argon into the vacuum furnace, controlling the temperature at 1200° C., and smelting for 3 hours to obtain a melt; semi-continuously casting the obtained melt to obtain a semi-continuous green sheet of a copper busbar;

[0083] Step (3), homogenizing the copper busbar semi-continuous billet at a temperature of 840° C., and then performing 2 cycles of 6 passes of cross rolling to obtain a copper busbar billet with uniform thickness; placing the copper busbar billet into a rapid die forging machine and pressing it into a copper busbar substrate of a specified shape;

[0084] Step (4), mechanically polishing the copper busbar substrate to make its surface roughness Ra≤0.15μm, then ultrasonically cleaning the copper busbar with ethanol, and then coating the thermal conductive anti-corrosion coating material on the copper busbar substrate, curing at 90°C for 2.5h, the thickness of the thermal conductive anti-corrosion coating after curing is 6μm, and a high-performance copper busbar is obtained.

[0085] Example 5

[0086] This embodiment discloses a method for preparing a high-performance copper busbar, comprising the following steps:

[0087] Step (1), mixing the composite aerogel and copper powder at a ratio of 0.5:100, and ball milling to obtain composite powder; ball milling conditions: grinding medium is stainless steel balls, ball-to-material ratio is 5:1, ball milling speed is 150 r / min, and ball milling time is 9 h;

[0088] Add scandium, chromium, lanthanum, cobalt, nickel, silicon, niobium and tantalum to the composite powder to obtain a mixed raw material, and crush the raw material into a mixed powder with a particle size of 40 mm; wherein the content of each component in the mixed powder is: scandium 0.25wt%, chromium 1.3wt%, lanthanum 0.1wt%, cobalt 1.1wt%, nickel 1.4wt%, silicon 0.65wt%, niobium 0.08wt%, tantalum 1wt%, and the rest is composite powder;

[0089] Step (2), pressing the mixed powder into a green sheet at 275 MPa, placing the green sheet into a vacuum furnace for smelting, introducing argon into the vacuum furnace, controlling the temperature at 1100° C., and smelting for 4 hours to obtain a melt; semi-continuously casting the obtained melt to obtain a semi-continuous green sheet of a copper busbar;

[0090] Step (3), homogenizing the copper busbar semi-continuous billet at a temperature of 810° C., and then performing 2 cycles of 4 passes of cross rolling to obtain a copper busbar billet with uniform thickness; placing the copper busbar billet into a rapid die forging machine and pressing it into a copper busbar substrate of a specified shape;

[0091] Step (4), mechanically polishing the copper busbar substrate to make its surface roughness Ra≤0.15μm, then ultrasonically cleaning the copper busbar with ethanol, and then coating the thermal conductive anti-corrosion coating material on the copper busbar substrate, curing at 80°C for 2h, the thickness of the thermal conductive anti-corrosion coating after curing is 4μm, and a high-performance copper busbar is obtained.

[0092] The thermal conductive anti-corrosion coating material in the above Examples 3-5 adopts the thermal conductive anti-corrosion coating material prepared in Example 1, and the composite aerogel adopts the composite aerogel prepared in Example 2.

[0093] Comparative Example 1

[0094] Comparative Example 1 Compared with Example 1, in the process of preparing the thermal conductive anti-corrosion coating material in Comparative Example 1, modified boron nitride is used instead of the composite hybrid, and other conditions remain unchanged.

[0095] Comparative Example 2

[0096] Compared with Example 1, in Comparative Example 2, during the preparation of the thermal conductive anti-corrosion coating material, no nano-alumina was added, and other conditions remained unchanged.

[0097] Comparative Example 3

[0098] Comparative Example 3 Compared with Example 2, in the process of preparing the composite aerogel in Comparative Example 3, MXene powder is used instead of modified MXene, and other conditions remain unchanged.

[0099] Comparative Example 4

[0100] Comparative Example 4 Compared with Example 4, in the process of preparing the composite aerogel in Comparative Example 4, no modified MXene was added, and other conditions remained unchanged.

[0101] Comparative Example 5

[0102] Compared with Example 5, Comparative Example 5 adopts the thermal conductive anti-corrosion coating material prepared in Comparative Example 1, and other conditions remain unchanged.

[0103] Comparative Example 6

[0104] Compared with Example 5, Comparative Example 6 adopts the thermal conductive anti-corrosion coating material prepared in Comparative Example 2, and other conditions remain unchanged.

[0105] Comparative Example 7

[0106] Comparative Example 7 Compared with Example 5, Comparative Example 7 uses the composite aerogel prepared in Comparative Example 3, and other conditions remain unchanged.

[0107] Comparative Example 8

[0108] Comparative Example 8 Compared with Example 5, Comparative Example 8 uses the composite aerogel prepared in Comparative Example 4, and other conditions remain unchanged.

[0109] Comparative Example 9

[0110] Comparative Example 9 Compared with Example 5, in the process of preparing the mixed powder in Comparative Example 9, no scandium was added, and other conditions remained unchanged.

[0111] Comparative Example 10

[0112] Compared with Example 5, in Comparative Example 10, no lanthanum was added during the preparation of the mixed powder, and other conditions remained unchanged.

[0113] Comparative Example 11

[0114] Compared with Example 5, in Comparative Example 11, no tantalum was added during the preparation of the mixed powder, and other conditions remained unchanged.

[0115] Comparative Example 12

[0116] Comparative Example 12 Compared with Example 5, in the process of preparing the mixed powder, copper powder is used instead of the composite aerogel, and other conditions remain unchanged.

[0117] In the above embodiments and comparative examples, boron nitride powder, purity: 99.9%, particle size: 10-15 μm, from Qinghe Chaotai Metal Materials Co., Ltd.; water-based epoxy resin, active ingredient content: 50%, appearance: liquid, model: ARALDITEPZ 756-1 / 67, density: 1.06 kg / m 3 , from Guangzhou Si Tu Yuan Chemical Co., Ltd.; nano alumina, appearance: white, particle size: 200 nanometers, sphericity: completely spherical, from Hangzhou Jiu Peng New Materials Co., Ltd.; wetting and dispersing agent, brand: Bick, purity: 99%, chemical composition: polyether siloxane copolymer, appearance: liquid, model: EFKA5210, from Shenzhen Huixin Plastic Chemical Co., Ltd.; polyether amine curing agent, appearance: colorless to light yellow liquid, density: 0.948g / cm 3 , boiling point: >200℃, flash point: 121℃, from Jinan Quanxing New Materials Co., Ltd.; defoamer BYK-072, main ingredients: foam-breaking polysiloxane solution, active ingredient content: 1%, appearance: liquid, density: 0.83kg / m 3, from Shanghai Dielin Chemical Co., Ltd.; leveling agent BYK-333, product name: BYK silicone surface additive, active ingredient content: 99%, appearance: colorless to light yellow viscous transparent liquid, density: 1kg / m 3 , purchased from Guangzhou Xinhuateng Technology Co., Ltd.; MAX phase Ti 3 AlC 2 Powder, CAS number: 196506-01-1, appearance: powder, active ingredient content: 99.5%, particle size / mesh: 2000 mesh, from Nangong Jiuxin New Material Technology Co., Ltd.

[0118] Experimental example

[0119] 1. The performance of the copper busbar substrates prepared in Examples 3-5 and Comparative Examples 7-12 was tested.

[0120] 1) Mechanical properties test:

[0121] According to the national standard "GB.T 228.1 Metallic material tensile test Part 1: Room temperature test method", the tensile strength and elongation at break are tested;

[0122] The hardness is tested according to the national standard "GB / T230.1 Metal Materials Brinell Hardness Test Part 1 Test Method".

[0123] 2) Conductivity test: Use a conductivity tester to test.

[0124] The test results are shown in Table 1:

[0125] Table 1

[0126] Tensile strength / MPa Hardness / HB Electrical conductivity / %IACS Example 3 380.5 112 109.4 Example 4 389.2 120 110.8 Example 5 384.8 115 109.9 Comparative Example 7 384.7 115 108.2 Comparative Example 8 376.4 110 107.4 Comparative Example 9 359.4 91 108.4 Comparative Example 10 372.1 105 106.1 Comparative Example 11 365.6 96 109.8 Comparative Example 12 341.9 98 105.3

[0127] From the test results in Table 1, it can be seen that the copper busbar matrix prepared in Examples 3-5 of the present invention has excellent mechanical properties and electrical conductivity. From the comparison of Comparative Examples 7-8 with Example 5, it can be seen that the deposition of nanosilver forms a better conductive path between the MXene nanosheets, thereby improving the conductivity of the MXene nanosheets, and the modified MXene exerts excellent electrical conductivity through the synergistic effect of nanosilver and MXene, thereby providing the conductivity of the copper busbar matrix; from the comparison of Comparative Examples 9-10 with Example 5, it can be seen that in the copper powder matrix, the combined doping of La and Sc produces a synergistic effect, resulting in high conductivity LaCu 6 Precipitates and high hardness ScCu 4 The formation of precipitates promotes high alloying and abundant dislocations, and can induce Ni with excellent mechanical properties. 2 Si and Co 2The formation of Si precipitates and the precipitation of NiSi phase with high conductivity can improve the mechanical properties and conductivity of the copper busbar; from the comparison of Comparative Example 11 and Example 5, it can be seen that the composite of tantalum and copper can refine the grains and improve the mechanical properties; from the comparison of Comparative Example 12 and Example 5, it can be seen that after grinding, the composite aerogel particles can work together through the two-scale reinforcement phase particles to greatly refine the grain structure of the copper busbar matrix, so that the copper busbar matrix has excellent conductivity and mechanical properties.

[0128] 2. The thermal conductivity and anti-corrosion performance of the high-performance copper busbars prepared in Examples 3-5 and Comparative Examples 5-6 were tested:

[0129] 1) Thermal conductivity test: refer to GB / T3651-2008;

[0130] 2) Corrosion resistance test: The test was conducted in accordance with the neutral salt spray test (NSS) recorded in GB / T10125 "Artificial atmosphere corrosion test salt spray test". The test results are shown in Table 2:

[0131] Table 2

[0132]

[0133]

[0134] From the test results in Table 2, it can be seen that the high-performance copper busbars prepared in Examples 3-5 of the present invention have good corrosion resistance and heat dissipation capabilities. From the comparison between Comparative Example 5 and Example 5, it can be seen that the intermediate product is connected to the surface of the modified boron nitride, and the phenolic hydroxyl group and amide group in the intermediate product can form hydrogen bonds with the epoxy resin, thereby improving the dispersibility of the modified boron nitride, and forming a strong interaction with the copper busbar matrix, improving the adhesion of the coating material, and making the coating material play a better effect; from the comparison between Comparative Example 6 and Example 5, it can be seen that the nano-scale aluminum oxide and the two-dimensional sheet structure of the composite hybrid material cooperate to form a more compact heat-conducting and anti-corrosion coating structure, and the spherical shape of the nano-alumina also helps to increase the surface roughness of the coating and enhance its hydrophobic properties, thereby improving the heat dissipation capacity and corrosion resistance of the copper busbar.

[0135] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-performance copper busbar, characterized in that: The following steps are involved: Step (1), mixing the composite aerogel with copper powder, ball milling to obtain composite powder; then adding scandium, chromium, lanthanum, cobalt, nickel, silicon, niobium and tantalum, crushing to obtain mixed powder; The preparation method of the composite aerogel comprises the following steps: Step B1, using MAX phase Ti3AlC2 powder as raw material to prepare MXene powder; modifying the MXene powder to obtain modified MXene; Step B2, first preparing silica aerosol, and then using the silica aerosol and modified MXene as raw materials to prepare a composite aerogel; Step (2), the mixed powder is pressed and smelted to obtain a melt; the melt is semi-continuously cast to obtain a semi-continuous billet of a copper busbar; Step (3), homogenizing the copper busbar semi-continuous billet, and then performing cross-rolling to obtain a copper busbar billet; the copper busbar billet is pressed to form a copper busbar matrix; Step (4), mechanically polishing and ultrasonically cleaning the copper busbar substrate, then coating the copper busbar substrate with a thermal conductive anti-corrosion coating material, and curing the coating to obtain a high-performance copper busbar; The preparation method of the thermal conductive anti-corrosion coating material comprises the following steps: Step A1, first prepare cerium carbonate, then react with methacrylic acid to obtain cerium methacrylate; modify boron nitride with cerium methacrylate to obtain modified boron nitride; Step A2, dopamine hydrochloride reacts with methacrylic anhydride to obtain an intermediate product; the intermediate product reacts with modified boron nitride to obtain a composite hybrid; Step A3, modifying the nano-alumina with 3-aminopropyltrimethoxysilane to obtain modified nano-alumina; A water-based epoxy resin and a composite hybrid are mixed, and then modified nano-alumina, a wetting dispersant, a polyetheramine curing agent, a defoaming agent, and a leveling agent are added to obtain a thermal conductive anti-corrosion coating material.

2. The method for preparing a high-performance copper busbar according to claim 1, characterized in that: In the step (1), the mass ratio of the composite aerogel to the copper powder is (0.3-0.6):100; the ball milling conditions are: the grinding medium is stainless steel balls, the ball-to-material ratio is 5:1, the ball milling speed is 100-200 r / min, and the ball milling time is 8-10 h.

3. The method for preparing a high-performance copper busbar according to claim 1, characterized in that: In the step (1), the particle size of the mixed powder is 20-50 mm; the contents of the components in the mixed powder are: scandium 0.1-0.4wt%, chromium 1-1.6wt%, lanthanum 0.05-0.15wt%, cobalt 0.8-1.4wt%, nickel 1.2-1.6wt%, silicon 0.5-0.8wt%, niobium 0.06-0.1wt%, tantalum 0.8-1.2wt%, and the rest are composite powders.

4. The method for preparing a high-performance copper busbar according to claim 1, characterized in that: In the step (2), the pressing pressure is 250-300 MPa; the smelting conditions are: temperature is 1000-1200° C., and time is 3-5 h.

5. The method for preparing a high-performance copper busbar according to claim 1, characterized in that: In the step (3), the temperature of the homogenization treatment is 780-840° C.; the copper busbar blank is obtained after 1-2 cycles of 3-6 passes of cross rolling.

6. The method for preparing a high-performance copper busbar according to claim 1, characterized in that: In the step (4), the copper busbar substrate is mechanically polished to have a surface roughness Ra≤0.15 μm.

7. The method for preparing a high-performance copper busbar according to claim 1, characterized in that: In the step (4), the curing conditions are: curing at 70-90° C. for 1.5-2.5 hours; the thickness of the thermal conductive anti-corrosion coating after curing is 2-6 μm.

8. The method for preparing a high-performance copper busbar according to claim 1, characterized in that: In the step (1), the method for preparing the composite aerogel comprises the following steps: Step B1, at room temperature, add MAX phase Ti3AlC2 powder to 48wt% hydrofluoric acid within 10-20min, stir for 20-40min, and then stir in an oil bath at 40-60°C for 12-15h. After the reaction, centrifuge, wash, and dry to obtain MXene powder; wherein the amount ratio of MAX phase Ti3AlC2 powder to hydrofluoric acid is (2-4)g:(40-100)mL; Add MXene powder to deionized water, and perform ultrasonic treatment for 20-40 minutes to obtain a suspension; dissolve silver nitrate in deionized water, and then add it to the suspension, stir and react in an ice bath for 100-150 minutes, collect the obtained precipitate, wash, and dry to obtain modified MXene; wherein the mass ratio of MXene powder to silver nitrate is (2.5-3.5):(0.05-0.1); Step B2, adding tetraethyl orthosilicate to ethanol, stirring for 10-20 minutes, adding ultrapure water, stirring for 20-40 minutes, adjusting the pH to 2 with a 0.1 mol / L sulfuric acid aqueous solution, stirring at 30-40° C. and 400-500 r / min for 1-2 hours to obtain a silica aerosol; wherein the mass ratio of tetraethyl orthosilicate, ethanol, and ultrapure water is (2.1-2.6):(2.3-2.8):(0.4-0.7); Add a 2 mg / mL modified MXene aqueous dispersion to the silica aerosol, adjust the pH to 7 with 0.5 mol / L ammonia water, stir for 10-15 min, seal, and stand at 40-50 ° C until the gel is complete to obtain a hybrid wet gel; the amount ratio of silica aerosol to modified MXene aqueous dispersion is (1.2-2.4) g: (12-36) mL; The hybrid wet coagulation is first immersed in an ethanol aqueous solution with a volume fraction of 80% and aged at a constant temperature of 48-52°C for 22-26h, then immersed in isopropanol and solvent exchanged at 38-42°C for 10-15h, then immersed in n-hexane and solvent exchanged at 38-42°C for 10-15h, the solvent is discharged, dried at room temperature for 12-36h, and then graded dried at 40-60°C and 100-120°C for 1.5-2.5h each to obtain a composite aerogel.

9. The method for preparing a high-performance copper busbar according to claim 1, characterized in that: In the step (4), the method for preparing the thermal conductive anti-corrosion coating material comprises the following steps: Step A1, under the stirring condition of 150-250r / min, cerium (III) nitrate hexahydrate, ammonium bicarbonate and deionized water are mixed, stirred at room temperature for 3-5h, filtered, washed and dried to obtain cerium carbonate; wherein the mass ratio of cerium (III) nitrate hexahydrate, ammonium bicarbonate and deionized water is (6-9):(3-5):(80-100); Add cerium carbonate and methacrylic acid into deionized water, stir and react at 85-95° C. and 150-250 r / min for 2-4 hours, and dry after the reaction to obtain cerium methacrylate; wherein the mass ratio of cerium carbonate, methacrylic acid and deionized water is (2-3):(4.5-6.5):(80-120); At 70-80° C., cerium methacrylate is dissolved in deionized water, and then boron nitride powder is added, stirred and reacted for 2.5-3.5 hours, and the solvent is distilled off to obtain modified boron nitride; wherein the mass ratio of cerium methacrylate, deionized water, and boron nitride powder is (1-3):(100-200):(6-8); Step A2, adding sodium borate and sodium bicarbonate to distilled water, and degassing with nitrogen bubbling for 20-40 minutes, and then adding dopamine hydrochloride to obtain a mixed solution; dissolving methacrylic anhydride in tetrahydrofuran, and then dripping it into the above mixed solution at a rate of 1-2mL / min, adjusting the pH of the reaction system to 8-8.5 with a sodium hydroxide aqueous solution having a concentration of 1 mol / L, stirring the reaction under nitrogen bubbling for 13-15 hours at room temperature to form a white slurry solution, washing with ethyl acetate 2-3 times, filtering, and purifying to obtain an intermediate product; wherein the mass ratio of sodium borate, sodium bicarbonate, distilled water, dopamine hydrochloride, methacrylic anhydride, and tetrahydrofuran is (10-20):(4-8):(100-200):(5-10):(4.7-9.4):(20-40); The intermediate product, azobisisobutyronitrile and modified boron nitride are added to N,N-dimethylformamide, the reaction mixture is bubbled with nitrogen for 20-40 minutes, and then the polymerization reaction is carried out at 55-65°C for 2.5-3.5 hours. After the reaction is completed, centrifugation, washing and drying are performed to obtain a composite hybrid; wherein the mass ratio of the intermediate product, azobisisobutyronitrile, modified boron nitride and N,N-dimethylformamide is (6-8):(0.04-0.08):(3-6):(100-250); Step A3, mixing ethanol and deionized water, adding 3-aminopropyltrimethoxysilane and nano-alumina, ultrasonically treating for 20-40 minutes, heating to reflux reaction for 10-12 hours, filtering, washing, and drying to obtain modified nano-alumina; wherein the mass ratio of ethanol, deionized water, 3-aminopropyltrimethoxysilane, and nano-alumina is (8-16):(40-80):(0.5-2.5):(2-5); In parts by weight, water-based epoxy resin and composite hybrid are mixed, stirred at a speed of 400-600 r / min for 20-40 min, then modified nano-alumina is added, stirred for 10-20 min, then a wetting dispersant is added, stirred for 20-30 min, a polyetheramine curing agent, a defoaming agent, and a leveling agent are added, stirred for 10-20 min, and a thermal conductive anti-corrosion coating material is obtained; Among them, the contents of each component in the thermal conductive anti-corrosion coating material are, by weight: 100-120 parts of water-based epoxy resin, 15-25 parts of composite hybrid, 5-15 parts of modified nano-alumina, 0.3-1.5 parts of wetting dispersant, 5-10 parts of polyetheramine curing agent, 0.5-1.3 parts of defoaming agent, 0.5-1.6 parts of leveling agent; the defoaming agent includes defoaming agent BYK-072, and the leveling agent includes leveling agent BYK-333.

10. A high-performance copper busbar prepared by the method for preparing a high-performance copper busbar according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Aerogel fireproof bus

    CN216215746U

  • Engineering of steady topology-controlled nanofibrous structures based on tissue engineering perspective

    WO2023073450A1